Twinfilin is a nonprocessive depolymerase which synergizes with formin to dramatically accelerate actin filament uncapping by 300-fold - Vishal Reddy; Ankita Arya; Shashank Shekhar (Proceedings of the National Academy of Sciences, 2025)
For over four decades, our understanding of cellular actin dynamics has been guided by the concept of treadmilling. However, this paradigm has been challenged by the evidence that twinfilin can uncap and promote depolymerization of filament barbed ends, though its precise mechanism remains debated. Using single-molecule microscopy and microfluidics-assisted TIRF imaging, we demonstrate that twinfilin transiently associates with barbed ends for ~0.2 to 0.5 s, acting as a nonprocessive depolymerase that likely removes one or both terminal actin subunits. Furthermore, we show that twinfilin’s barbed-end residence time and its ability to uncap CP-capped filaments (both alone and with formin mDia1) are significantly influenced by filament age. The synergistic enhancement in uncapping by twinfilin and mDia1 ranges from 11-fold for newly assembled to ~318-fold for aged actin filaments. These represent the fastest uncapping rates measured in vitro and approach CP turnover rates in vivo. Our study thus reinforces twinfilin’s central role as a multifunctional barbed-end regulator which nonprocessively depolymerizes actin filaments, transiently caps barbed ends, and synergizes with formin to destabilize CP, thereby facilitating rapid actin turnover that depends on filament age.